The Influence of Brand Image and Online Customer Review On Purchasing Decisions In Tokopedia E-Commerce In Bekasi Regency With Buying Interest As A Mediating Variable - Ade Subakti; Adibah Yahya; Susan Kustiwan (Dinasti International Journal of Education Management And Social Science, 2024)
The advancement of the digital technology era supports an increasingly modern way of consumer shopping, this is in accordance with various events that exist in today's society, one of which is offline shopping which has turned into online shopping. The purpose of this study is to create and develop an empirical conceptual model of how brand image and online customer review of purchasing decisions in Tokopedia E-commerce in Bekasi Regency with purchase interest become mediation variables. The results of the analysis concluded that brand image has a positive influence on purchasing decisions. Brand image has a positive influence on buying interest. Online customer reviews have a positive influence on purchasing decisions. Online customer reviews have no effect on buying interest. Buying interest has a positive effect on purchasing decisions. Brand image positively influences purchasing decisions mediated by purchase interest. Online customer reviews have no influence on the buyer's decision.